1992
DOI: 10.2307/1591759
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Oncogenic and Nononcogenic Strains of Marek's Disease Virus Type 1 by Using Polymerase Chain Reaction DNA Amplification

Abstract: Differentiation of oncogenic and nononcogenic strains of Marek's disease virus type 1 (MDV1) was attempted by polymerase chain reaction (PCR) using the primers chosen from the sequence within the long inverted repeats of MDV1 DNA. PCR of the DNAs extracted from oncogenic-strain-infected cells and Marek's disease tumor cell lines produced a major product containing two or three copies of 132-base-pair (bp) repeat units, whereas PCRs of the DNAs extracted from nononcogenic-strain-infected cells yielded amplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…MD commonly appears in 3-4 week old chickens and gradually builds to a peak between 12 and 30 weeks of age. Polymerase chain reaction (PCR) has emerged in recent years as an additional diagnostic tool offering the advantages of serotype specificity and the ability to differentiate between vaccinal and field strains of MDV serotype-1 [4,8,12]. The importance of BamHI-H region in the pathogenesis of MDV was initially pointed out; when it was shown that there was an increase in the number of copies of 132 bp repeats within the BamHI-H region of inverted repeats (IR) as a result of attenuation by cell culture passage [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MD commonly appears in 3-4 week old chickens and gradually builds to a peak between 12 and 30 weeks of age. Polymerase chain reaction (PCR) has emerged in recent years as an additional diagnostic tool offering the advantages of serotype specificity and the ability to differentiate between vaccinal and field strains of MDV serotype-1 [4,8,12]. The importance of BamHI-H region in the pathogenesis of MDV was initially pointed out; when it was shown that there was an increase in the number of copies of 132 bp repeats within the BamHI-H region of inverted repeats (IR) as a result of attenuation by cell culture passage [9].…”
mentioning
confidence: 99%
“…amplification of 132 bp repeats) in MDV type-1 as an indicator for critical genomic rearrangement leading to the attenuation of virus virulence. In a similar study, Zhu et al [12] differentiated the oncogenic and non-oncogenic strain of MDV-1 by primer chosen from the sequence within the long inverted repeats of MDV-1 DNA.…”
mentioning
confidence: 99%
“…This transcript is mapped in the internal repeat long (IRL) region of the MDV genome containing the tandem repeats of the 132-bp repeat region. This repeat region is expanded during attenuation by in vitro passage and also found in vaccine strain CVI988 [21,22]. Recently, it was shown that the expansion of the 132-bp repeat is not sufficient in itself to attenuate pathogenic MDV [23].…”
Section: Introductionmentioning
confidence: 99%
“…This repeat region is expanded during in vitro passage and the 1.8-kb mRNA becomes disrupted and heterogeneous [9]. In virulent oncogenic strains of MDV, there are only two copies of the 132-bp but are multiple copies up to 100 in attenuated viruses [16,17]. For a very long time, it was suggested that the expansion of the 132-bp region, disrupts the 1.8-kb mRNA that is essential for oncogenicity, thereby resulting in attenuation [9,18].…”
Section: Introductionmentioning
confidence: 99%